ANALISIS KINERJA KPRI SEGAR BREBES DITINJAU DARI LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS. - Lusia Wulandari Sutejo (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2017)
ABSTRACT This study aims to determine the analysis of financial performance at KPRI Segar Brebes. The subject of this study is the financial performance of KPRI Segar Brebes in terms of liquidity, solvency, and profitability, the data sources used are secondary data obtained from data or records from examiners' reports on financial statements arranged in archives or books obtained from KPRI Segar Brebes. This study uses a quantitative descriptive approach. The results of the study show that assets that are sufficiently liquid in paying their short-term obligations. With conditions, the level of solvency is bad and the level of profitability is in good condition. Keywords : liquidity ratio, solvency ratio,profitability ratio